"Because I've Got a Learning Disability, They Don't Take Me Seriously:" Violence, Wellbeing, and Devaluing People With Learning Disabilities. Issue 13 (July 2022) - Wiseman, Phillippa; Watson, Nick
For people with learning disabilities, targeted violence has become routinized. In this article, we seek to explore the impact pervasive victimization has on their experience of community and participation and, through this, their health and wellbeing. People with learning disabilities experience significant inequality in health and wellbeing compared to their non-disabled peers, and the role of violence and victimization remains mostly neglected. By drawing on in-depth qualitative interviews with people with learning disabilities, we argue that abuse, disrespect and devaluing profoundly erode wellbeing. The complex forms of violence experienced by people with learning disabilities are critical to understanding the significant inequalities in health and wellbeing experienced by people with learning disabilities. We focus on community and misrecognition to move the focus from one that examines causation towards one that uncovers the layers of invisibility, and the complex relations that structure experiences from the perspective of people with learning disabilities themselves. By doing this, we locate violence and victimization as health and wellbeing concerns and seek to add a more comprehensive and holistic understanding of the social determinants of health. For the inequalities that structure the lives of people with learning disabilities to be holistically understood, they must be reframed as an issue of social justice, and violence must be identified as a central contributor to these inequalities.